Stationary echosounder (EK60, Simrad, 38 & 200 kHz) recordings from the central Red Sea near Thuwal, Saudi Arabia, between January 2014 and February 2016 - Svenja Christiansen; Anders Røstad; Stein Kaartvedt (PANGAEA, 2023)
Simrad EK60 echosounders (38 and 200 kHz) were deployed in the central Red Sea during several multiple-days periods between January 2014 and February 2016. Records were made in the deepest part of a ~700 m deep basin (22.5°N, 39.03°E) referred to as the Economic City Deep (ECDEEP) and at ~555 m along its sloping edge, and at a nearby 880 m deep station (22.08?N, 38.71?E). All locations were situated near the King Abdullah University of Science and Technology (KAUST) campus, Saudi Arabia. In the events marked by "bottom-mounted deployment" the echosounders were deployed on the bottom facing the surface. The floating mooring was connected to concrete weights by steel wires ensuring vertical orientation such that the transducers were located ca. 7 m off the bottom. The bottom-mounted deployments continuously recorded the movement and abundance of scattering layers and organisms over depth and time at a time resolution of ~0.5 pings/s. In the events marked by "profile", the echosounders were deployed facing downwards in a profile stopping at different depths for each ca. 15-30 minutes. During the profiles, a tungsten carbide (38.1 mm; theoretical target strength -42.3 dB and -38.9 dB on 38 and 200 kHz, respectively) calibration sphere was attached 10 m or 16 m below the echosounder rig as target strength reference. The dataset contains 12 events with in total 1317 raw proprietary Simrad EK60 data files with file sizes between 0.7 and 168 MB. The raw files include transducer configuration data and sample data (raw power (W) and angles (alongship and athwartship, °)).